2011
DOI: 10.1111/j.1365-3156.2011.02848.x
|View full text |Cite
|
Sign up to set email alerts
|

Integrated tuberculosis and HIV care in a resource‐limited setting: experience from the Martin Preuss centre, Malawi

Abstract: Summary Objectives  To describe the development and operation of integrated tuberculosis (TB) and HIV care at the Martin Preuss Centre, a multipartner organization bringing together governmental and non‐governmental providers of HIV and TB services in Lilongwe, Malawi. Methods  We used a case study approach to describe the integrated TB/HIV service and to illustrate successes and challenges faced by service providers. We quantified effective TB and HIV integration using indicators defined by the World Health O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 3 publications
(3 reference statements)
1
23
1
Order By: Relevance
“…Twelve studies evaluated ART coverage. Nine [27][28][29][30][31][32][33][34][35] reported improved coverage, and three [36][37][38] reported similar coverage, when ARTwas provided in TB care settings versus separate services (Fig. 2).…”
Section: Antiretroviral Therapy Integration With Tuberculosis Treatmementioning
confidence: 99%
“…Twelve studies evaluated ART coverage. Nine [27][28][29][30][31][32][33][34][35] reported improved coverage, and three [36][37][38] reported similar coverage, when ARTwas provided in TB care settings versus separate services (Fig. 2).…”
Section: Antiretroviral Therapy Integration With Tuberculosis Treatmementioning
confidence: 99%
“…16,17 The benefits of integration (and of the implementation of the 2010 WHO ART guidelines) have been shown to accelerate the uptake of ART and reduce delays in starting this life-saving treatment. [17][18][19][20][21][22][23][24][25][26] However, most of these studies have been conducted outside the realm of rural, resource-constrained public health facilities. The operational impact on treatment outcomes has also been inconsistent.…”
mentioning
confidence: 99%
“…For instance, integration of HIV care with tuberculosis (TB) and sexually transmitted infection (STI) services in Haiti showed demonstrable increases in patient access, uptake of testing and case detection, enrollment in antiretroviral therapy (ART), and even benefits in unrelated programs such as vaccine coverage [25-27]. Similar results with TB/HIV integration have demonstrated improved rates of screening [28,29] increased enrollment in antiretroviral treatment programs [30], and even improved TB treatment outcomes in one cohort in Ghana [31], but a recent systematic review of TB/HIV integration suggested that more robust downstream outcome measures should be emphasized in future research [32]. Research has also been conducted on integration of HIV care and treatment services with programs such as Prevention of Mother to Child Transmission (PMTCT) [33] and family planning services [34-36], with generally positive results with respect to patient access, and patient and provider perceptions.…”
Section: Discussionmentioning
confidence: 99%